Pulmonary passport: a service evaluation study of a standardised web-based procedure logbook to aid specialist respiratory training and appraisal. Issue 1 (12th November 2020) - Cheng, Andrew; Saba, Tarek; Duncan, Tracy; Grundy, Seamus; Evison, Matthew
Abstract : Introduction: The pulmonary passport (PP) is a secure web-based procedural logbook for specialist respiratory trainees with enhanced functionality that includes automated analysis to provide key performance metrics and in-platform interactions with supervisors. Methods: This service evaluation study used preimplementation and postimplementation online surveys in both trainees and supervisors along with analysis of recorded data within the PP to evaluate the impact of this service on data capture, training, appraisal and quality assurance. Results: From August 2017 to August 2019, 69/73 (95%) specialist respiratory trainees eligible to use the PP across two UK health education deaneries registered with the system and logged 7352 procedures. 3105 thoracic ultrasound procedures identified 2145 pleural effusions and resulted in 1253 pleural procedures of which 96% were successful. 4% of ultrasounds required referral to a more expert sonographer. Iatrogenic bleeding and pneumothorax both occurred in ≤1% of all pleural procedures. 1909 basic diagnostic bronchoscopies were recorded including 1236 bronchial washes, 328 brushes and 221 endobronchial biopsies where definite tumour was identified (biopsy sensitivity 74%). Preimplementation and postimplementation survey data confirmed the PP had increased the consistency of logging procedures by trainees, the depth of data captured, the review of procedural performance metrics in appraisal and the frequency of formal supervisor feedback. Discussion: In this regional project, the implementation of a web-based procedural logbook has been feasible with excellent uptake and has enhanced procedural recording, supervision and appraisal. Furthermore, it provides unprecedented quality assurance at an individual trainee, trust and deanery level and has a number of potential wider applications in the future.